Exploring the Relationship Between Psychiatric Traits and the Risk of Mouth Ulcers Using Bi-Directional Mendelian Randomization - Wang, Kai; Ding, Lin; Yang, Can; Hao, Xingjie; Wang, Chaolong (Frontiers in Genetics, 2020)
Background: Although the association between mouth ulcers and psychiatric traits has been reported by observational studies, their causal relationship remains unclear. Mendelian randomization (MR), powered by large-scale genome-wide association studies (GWAS), provides an opportunity to clarify the causality between mouth ulcers and psychiatric traits. Methods: We collected summary statistics of mouth ulcers (sample size n=461,106) and ten psychiatric traits from the largest publicly available GWAS on Europeans, including anxiety disorder (n=83,566), attention deficit/hyperactivity disorder (n=53,293), autism spectrum disorder (n=46,350), bipolar disorder (n=51,710), insomnia (n=1,331,010), major depressive disorder (n=480,359), mood instability (n=363,705), neuroticism (n=168,105), schizophrenia (n=105,318), and subjective wellbeing (n=388,538). We applied three two-sample bi-directional MR analysis methods, namely the Inverse Variance Weighted (IVW) method, the MR pleiotropy residual sum and outlier (MR-PRESSO) method, and the weighted median method, to assess the causal relationship between each psychiatric trait and mouth ulcers. Results: We found significant effects of autism spectrum disorder, insomnia, major depressive disorder, and subjective wellbeing on mouth ulcers, with corresponding odds ratio (OR) from the IVW method being 1.160 (95% confidence interval [CI]: 1.066-1.261, P=5.39×10-4), 1.092 (1.062-1.122, P=3.37×10-10), 1.234 (1.134-1.342, P=1.03×10-6), and 0.703 (0.571-0.865, P=8.97×10-4), respectively. We also observed suggestive evidence for mood instability to cause mouth ulcers [IVW, OR=1.662 (1.059-2.609), P=0.027]. These results were robust to weak instrument bias and heterogeneity. We found no evidence on causal effects between other psychiatric traits and mouth ulcers, in either direction. Conclusion: Our findings suggest a protective effect of subjective wellbeing and risk effects of autism spectrum disorder, insomnia, major depressive disorder, and mood instability on mouth ulcers. These results clarify the causal relationship between psychiatric traits and the development of mouth ulcers.